2003
DOI: 10.1007/s000180300049
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide mediates growth inhibition of the Plasmodium falciparum parasite

Abstract: In mammalian cells, ceramide mediates death by chemotherapeutic drugs. We analysed, for the first time, the role of ceramide in inhibiting growth of the malaria-causing parasite Plasmodium falciparum. Added exogenously, ceramide significantly decreased the number of parasites, and this effect was abolished by sphingosine-1-phosphate, a biological antagonist of ceramide action. Ceramide can induce death of cancer cells by decreasing glutathione levels, and in our work it induced dose- and time-dependent depleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 59 publications
1
46
0
Order By: Relevance
“…3E). Cer can be synthesized from host SM by the parasite sphingomyelinase (49) and can induce Plasmodium growth inhibition (54). Thus, Cer needs to be maintained at low physiological levels, as observed in our analysis (Fig.…”
Section: Resultsmentioning
confidence: 61%
“…3E). Cer can be synthesized from host SM by the parasite sphingomyelinase (49) and can induce Plasmodium growth inhibition (54). Thus, Cer needs to be maintained at low physiological levels, as observed in our analysis (Fig.…”
Section: Resultsmentioning
confidence: 61%
“…In a recent review article, Deponte and Becker have reported TUNEL activity in P. falciparum blood-stage schizonts treated with antimalaria drugs and H 2 O 2 (7). Other studies have failed to detect TUNEL-positive assay results in P. falciparum parasites treated in vitro with known antimalarial drugs (38,39). Taken together, the presence of "crisis forms" and TUNEL-positive parasites suggests that febrile temperature-induced parasite killing is mediated by the mechanism of apoptotic cell death.…”
Section: Resultsmentioning
confidence: 91%
“…As a consequence, targeting SMase, SMS, and/or GCS could inhibit growth of the parasite (14,73). Conversely, excessive accumulation of ceramide may also be detrimental for the pathogen since treatment with exogenous ceramide inhibits parasitic growth through a nonapoptotic mechanism (71,109). Indeed, the antimalarial drugs artemisinin and mefloquine may exert their antiparasitic effects through the activation of SMase (109).…”
Section: Fig 2 Sphingolipid Biosynthetic Pathwaysmentioning
confidence: 99%
“…Conversely, excessive accumulation of ceramide may also be detrimental for the pathogen since treatment with exogenous ceramide inhibits parasitic growth through a nonapoptotic mechanism (71,109). Indeed, the antimalarial drugs artemisinin and mefloquine may exert their antiparasitic effects through the activation of SMase (109). The consequent increase of ceramide would decrease the level of glutathione, thereby preventing degradation of ferroprotoporfirin IX, which is toxic to plasmodia.…”
Section: Fig 2 Sphingolipid Biosynthetic Pathwaysmentioning
confidence: 99%